Effect of mode of delivery and infant's age on the fatty acid composition of human milk - Intonen, Linda (My University, 2020)
Human milk is the sole source of nutrition for a growing infant. It has all the nutrients the infant needs in the first six months of life. Lipids are the component in milk that supply the infant with approximately 50 % of daily dietary energy. Lipids appear in milk as fat globules in which triacylglycerols form the inner core of the globule and phospholipids serve as membrane lipids.. During growth of the infant, the composition of milk changes to adapt to the infant’s needs. The fat content of milk increases during lactation, and individual amounts of fatty acids also change. The effect of diet, nationality, age of the mother and gestational age on the fatty acid profile has been studied before, whereas the impact of mode of delivery has been less investigated. A total of 43 breast-feeding mothers from a larger study cohort were drawn for this study. Two breast milk samples were collected by the mothers; the first one when the infant was less than 15 days old and the second one when the infant was between 1-2 months old. The mothers were grouped according to the mode of delivery. The aim of this thesis work was to analyze the changes of the fatty acid composition of human milk during lactation and to determine the effect of delivery mode on fatty acid composition. The milk fat was extracted with 2:1 v/v chloroform-methanol and triacylglycerol-rich and phospholipid-rich fractions were separated by solid phase extraction. Fatty acid methyl esters were analyzed by gas chromatography. Results showed that minor differences were observed in the triacylglycerol-rich fraction of the milk fat while more significant variations were recognized in the phospholipid-rich fraction between vaginal delivery and caesarean section. On average, the milk of mothers who had delivered with a caesarean section contained less saturated fatty acids at the first time point compared to the vaginal delivery group. As human milk varies in composition due to many influences, the effect of for example diet should also be accounted for when explaining these results.
Keywords: fatty acid, human milk, gas chromatography